Chemopreventive Effects And Proteomic Analysis Of Myo Inositol Treatment On Human Prostate Cancer Cell Line (Du-145) - Islam, Mohammad Jahidul (2022)
Prostate cancer remains the second most frequent diagnosed cancer in men and is the third leading cause of cancer related death, despite many available treatment options. The inefficiency of existing therapies and their adverse effects have led scientists to seek new treatments for this disease. The identification and development of new anti-proliferative agents for prostate cancer is a major innovation in treating this deadly disease. Although the synthetic compound Myo-inositol is widely used in cancer research, the actual anti-cancer function of these chemicals is still not well understood. This study was therefore intended to unveil the chemopreventive effects of Myo-inositol on prostate cancer cells (DU-145). The growth inhibitory effect and the IC50 value were demonstrated by Myo-inositol at 0.06 mg/ml (**p<0.05). It is suspected that cell deaths are related to apoptosis induction and cell-cycle arrest. Treatment with Myo-inositol has been further identified by induction of early and late apoptosis (***p<0.01). Apoptosis can also be detected using DNA fragmentation and Hoechst 33342 fluorescent dye stain analysis. Myo-inositol caused an alteration to the cell cycle regulation on DU-145 cell line at G0/G1 and S phase, respectively (***p<0.01). Protein identification results via 2D electrophoresis and LC-MS/MS analysis showed 19 and 23 proteins identified in control and Myo-inositol treated samples, respectively.